The Vector Population Monitoring Tool (VPMT): High-Throughput DNA-Based Diagnostics for the Monitoring of Mosquito Vector Populations. (2nd December 2010) - Bass, Chris; Nikou, Dimitra; Vontas, John; Donnelly, Martin J.; Williamson, Martin S.; Field, Linda M.
Abstract : Regular monitoring of mosquito vector populations is an integral component of most vector control programmes. Contemporary data on mosquito species composition, infection status, and resistance to insecticides are a prerequisite for effective intervention. For this purpose we, with funding from the Innovative Vector Control Consortium (IVCC), have developed a suite of high-throughput assays based on a single "closed-tube" platform that collectively comprise the "Vector Population Monitoring Tool" (VPMT). The VPMT can be used to screen mosquito disease vector populations for a number of traits including Anopheles gambiae s.l. and Anopheles funestus species identification, detection of infection with Plasmodium parasites, and identification of insecticide resistance mechanisms. In this paper we focus on the Anopheles -specific assays that comprise the VPMT and include details of a new assay for resistance todieldrin Rdl detection. The application of these tools, general and specific guidelines on their use based on field testing in Africa, and plans for further development are discussed.